DHODH modulates immune evasion of cancer cells via CDP-Choline dependent regulation of phospholipid metabolism and ferroptosis - Da Teng; Kenneth D. Swanson; Ruiheng Wang; Aojia Zhuang; Haofeng Wu; Zhixin Niu; Li Cai; Faith R. Avritt; Lei Gu; John M. Asara; Yaqing Zhang; Bin Zheng (Nature Communications)
Abstract The ability of cancer cells to evade immune destruction is governed by various intrinsic factors including their metabolic state. Here we demonstrate that inactivation of dihydroorotate dehydrogenase (DHODH), a pyrimidine synthesis enzyme, increases cancer cell sensitivity to T cell cytotoxicity through induction of ferroptosis. Lipidomic and metabolomic analyses reveal that DHODH inhibition reduces CDP-choline level and attenuates the synthesis of phosphatidylcholine (PC) via the CDP-choline-dependent Kennedy pathway. To compensate this loss, there is increased synthesis from phosphatidylethanolamine via the phospholipid methylation pathway resulting in increased generation of very long chain polyunsaturated fatty acid-containing PCs. Importantly, inactivation of Dhodh in cancer cells promotes the infiltration of interferon γ-secreting CD8+ T cells and enhances the anti-tumor activity of PD-1 blockade in female mouse models. Our findings reveal the importance of DHODH in regulating immune evasion through a CDP-choline dependent mechanism and implicate DHODH as a promising target to improve the efficacy of cancer immunotherapies.